Strategy Of Rural Area Development Based On Plantation Agribusiness - Muhammad Buhari Sibuea; Muhammad Thamrin; Mardiati Mardiati; Arry Wihardi Pratama (JASc (Journal of Agribusiness Sciences), 2020)
This study aims to determine the development strategy of rural area based on agro-business of smallholder palm oil plantation in the Teladan Baru village of Rundeng Subulussalam City, making plans for the development of the region.  Teladan Baru is a village that has potential in oil palm plantations, almost all communities own oil palm plantations. But the production of most farmers is below average and  will affect to income of farmers also, this condition will cause the condition of farmers is still difficult to develop. Therefore an alternative strategy for rural development is needed, one of which is to open new land to increase the income of farmers who will automatically develop rural areas.